2019
DOI: 10.21037/acs.2019.06.07
|View full text |Cite
|
Sign up to set email alerts
|

Arch and access vessel complications in penetrating aortic ulcer managed with thoracic endovascular aortic repair

Abstract: Background: To analyze our experience and to describe access and arch-related challenges when performing thoracic endovascular aortic repair (TEVAR) for penetrating aortic ulcers (PAUs). Methods: This is a single-center, observational, cohort study. Between October 2003 and February 2019, 48 patients with PAU were identified; 37 (77.1%) treated with TEVAR were retrospectively analyzed. Primary major outcomes were early (<30 days) and late survival, freedom from aortic-related mortality (ARM), and a composite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The main difference here is that PAU is an obliterative aortic disease that makes these patients prone to multisite arterial disease such as coronary artery disease, carotid artery disease or peripheral arterial disease. Consequently, procedural risk, in particular for access vessel challenges, and most importantly for stroke, is higher [10]. It remains of utmost importance to anticipate risk during screening and to link findings of preoperative imaging to the potential complications caused by wire manipulation early and to rethink the treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The main difference here is that PAU is an obliterative aortic disease that makes these patients prone to multisite arterial disease such as coronary artery disease, carotid artery disease or peripheral arterial disease. Consequently, procedural risk, in particular for access vessel challenges, and most importantly for stroke, is higher [10]. It remains of utmost importance to anticipate risk during screening and to link findings of preoperative imaging to the potential complications caused by wire manipulation early and to rethink the treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a recent study published by Piffaretti et al, a cohort of 48 patients with PAUs were reported, 37 of them treated with TEVAR. 17 In this study, a proximal sealing zone of a minimum of 15 mm was required. Adjunctive procedures within the arch (carotid subclavian bypasses, LSA chimney, and supra-aortic trunk debranching) were performed in 7 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Complications related to the femoral artery access sites are also common 25 . The femoral arteries are cuff down to deploy the stent graft in most of the patients in our center.…”
Section: Discussionmentioning
confidence: 99%